[ 6·(12: x+ 56): 3- 18] ·7+ 78= 792
[ 6·(12: x+ 56): 3- 18] ·7 = 792- 78
[ 6·(12: x+ 56): 3- 18] ·7 = 714
[ 6·(12: x+ 56): 3- 18] = 714:7
6·(12: x+ 56): 3- 18 = 102
6·(12: x+ 56): 3 = 102+ 18
6·(12: x+ 56): 3 = 120
6·(12: x+ 56) = 120·3
6·(12: x+ 56) = 360
(12: x+ 56) = 360: 6
12: x+ 56 = 60
12 : x = 60- 56
12 : x = 4
x =12:4
x = 3
probă: [ 6·(12: 3+ 56): 3- 18] ·7+ 78= 792
[ 6·( 4+ 56): 3- 18] ·7+ 78= 792
( 6· 60: 3- 18) ·7+ 78= 792
( 360:3- 18 )·7+ 78 = 792
( 120-18)·7+ 78 = 792
102·7+ 78 = 792
714 + 78 = 792
792 = 792